2012
DOI: 10.1182/blood.v120.21.948.948
|View full text |Cite
|
Sign up to set email alerts
|

Significant Improvement of the Survival of Patients with Multiple Myeloma Presenting with Severe Renal Impairment After the Introduction of Novel Agents

Abstract: 948 Renal impairment (RI) is a common presenting complication of multiple myeloma (MM) and is associated with increased risk of treatment related toxicity and early death. The management of RI in patients with MM requires vigorous supportive measures and the immediate institution of antimyeloma therapy. After the introduction of novel agents a significant improvement of the survival of patients with MM has been observed; however, the impact of these therapies on the survival of MM patients who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 0 publications
3
29
1
1
Order By: Relevance
“…Our study confirms the findings from a retrospective review of patients treated in Greece [21]. While the introduction of novel agents improved survival outcomes for all patients including those with RI, patients with both moderate and severe RI had worse survival than those without this comorbidity [21]. While studies examining the prognostic relevance of CVD in patients with MM could not be found, in this analysis, the risk of death increased by 75% among patients with CVD alone and it almost doubled among those with concomitant CVD and RI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study confirms the findings from a retrospective review of patients treated in Greece [21]. While the introduction of novel agents improved survival outcomes for all patients including those with RI, patients with both moderate and severe RI had worse survival than those without this comorbidity [21]. While studies examining the prognostic relevance of CVD in patients with MM could not be found, in this analysis, the risk of death increased by 75% among patients with CVD alone and it almost doubled among those with concomitant CVD and RI.…”
Section: Discussionsupporting
confidence: 91%
“…Patients presenting with CVD and/or RI at first relapse had significantly shorter OS from time of initiation of second line therapy. Our study confirms the findings from a retrospective review of patients treated in Greece [21]. While the introduction of novel agents improved survival outcomes for all patients including those with RI, patients with both moderate and severe RI had worse survival than those without this comorbidity [21].…”
Section: Discussionsupporting
confidence: 87%
“…It is possible that potential prognostic differences related to the amyloidogenicity of light chains in intratubular amyloid patients could have been obscured by the generally bad outcome of light chain cast nephropathy. However, it should be noted that the renal prognosis of multiple myeloma patients is improving, 31,32 likely due to more effective chemotherapy molecules, such as thalidomide and bortezomib, 33 and the use of new dialysis techniques to remove free light chains. 34 Our results suggest that the detection of intratubular amyloid could help to identify light chain cast nephropathy patients at risk of developing systemic light chain amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patient comorbidities have been associated with higher mortality in various clinical trials of patients with MM . For some patients with MM, comorbidities are a direct cause of death, but they also put patients at risk for early disease‐related mortality by compromising the ability to effectively give treatment . Although the 6.8% incidence of EM observed in this study suggests the benefit of novel agents and improved supportive care, there are several issues to be noted.…”
Section: Discussionmentioning
confidence: 99%